Sebuah Aspek Sosial dan Stigma pada Anak dengan Epilepsi : Sebuah Literature Review - Amti Miftakhur Rizki; Roro Rukmi Windi Perdani; Linda Septiani; Anggi Setiorini (CV. Jasa Sukses Abadi, 2026)
Epilepsy in children not only results in neurological impairments but also carries a significant psychosocial burden, with social stigma emerging as a major challenge affecting quality of life. This literature review aims to explore the forms of stigma, social impacts, contributing factors, and strategies to mitigate stigma in children with epilepsy by analyzing published research. The literature search was conducted through PubMed, Google Scholar, and Scopus, focusing on articles published between 2020 until 2025. Findings from the review indicate that stigma is experienced by approximately one-third of children and adolescents with epilepsy (34%–35.6%), showing consistent patterns across countries such as Tiongkok, Uganda, and Turki. Stigma is significantly correlated with increased psychological distress and reduced self-esteem. Factors such as lack of formal education (62% stigma rate in Uganda), low family income, and higher seizure frequency were found to exacerbate stigma levels. The impact of stigma also extends to parents, contributing to health fatalism the belief that health outcomes are predetermined and cannot be changed. However, physical activity has been identified as a mediating factor that can reduce the negative psychological consequences of stigma. Overall, stigma represents a universal issue that adversely affects the mental health of children with epilepsy and their families. A holistic approach combining seizure control with psychosocial interventions including public education, school-based support, and promotion of physical activity is essential to combat stigma and improve quality of life.